Study on the Optical Properties of Triangular Cavity Absorber for Parabolic Trough Solar Concentrator - Fei Chen; Ming Li; Reda Hassanien Emam Hassanien; Xi Luo; Yongrui Hong; Zhikang Feng; Mengen Ji; Peng Zhang (International Journal of Photoenergy)
A theoretical analytical method for optical properties of cavity absorber was proposed in this paper and the optical design software TracePro was used to analyze the optical properties of triangular cavity absorber. It was found that the optimal optical properties could be achieved with appropriate aperture width, depth-to-width ratio, and offset distance from focus of triangular cavity absorber. Based on the results of orthogonal experiment, the optimized triangular cavity absorber was designed. Results showed that the standard deviation of irradiance and optical efficiency of optimized designed cavity absorber were 30528 W/m2 and 89.23%, respectively. Therefore, this study could offer some valuable references for designing the parabolic trough solar concentrator in the future.